The impact of coping strategies of cancer caregivers on psychophysiological outcomes: an integrative review - Teixeira, Ricardo João (2018)
A growing number of studies have explored the psychosocial burden experienced by cancer caregivers, but less attention has been given to the psychophysiological impact of caregiving and the impact of caregivers' coping strategies on this association. This paper reviews existing research on the processes underlying distress experienced by cancer caregivers, with a specific focus on the role of coping strategies on psychophysiological correlates of burden.